The Effect of Using Animation Video Learning Media To Results Study Fiqh Class VII in MTs Country 5 Bantul Yogyakarta - Dianda Nur Istiqomah; Yuli Kuswadari; Eva Latipah; Radino (Insight School Academy, 2023)
Introduction to The Problem : The background of this research is that the results of learning Fiqh are less than satisfactory at MTs Negeri 5 Bantul. One of the contributing factors is That the condition of the class needs to be more conducive. Educators endeavor to present learning, which is a more interesting use of animated learning media because playful media is an appropriate means of conveying knowledge with character participants educated for increased results Study Fiqh. Purpose : This research aims to find out whether video media is used. Animation learning influences students' learning outcomes in Jurisprudence and how much greater the effect is compared to conventional classes. Design/methods/approach: Study This uses the Quasi experiment method. Method with design pre-post control-experiment. Subject study This is para student class VII NTs Country 5 Bantul, Good man And Woman totaling 64 people, who were divided into two groups, namely 32 people entered the experimental class and 32 people in the control group. Data collection using the test method with instruments of Jurisprudence questions according to class VII material. The test used is a multiple choice test in the pretest and posttest in the experimental and control classes. The data analysis technique uses the paired tmethod test SPSS 21 And N-gain. Findings : Results show an influence of media learning video animation on results Study Fiqh on class VII students at MTs Negeri 5 Bantul. This showed from the results analysis test paired t test SPSS 21 class experiment as class Which given treatment form application media learning videos animation with mark t = 9,715 mark significance p as big as 0,000 And class control with learning conventional with mark t = 8,903 And mark significance 0,000 (0.000<0.05). Based on Test Ngain obtained enhancement average class experiment as big as 69.9% It means including category learning effective Enough, whereas class control as big as 51.8% including in category learning not effective enough. Based on R 2, it obtained a mark as big as 69.9%, Which means that video animation contributes to results. Study fiqh is as big as 18 %, and the rest is influenced by variables that were not examined in this study. So, media use learning video animation is more influential from learning conventional to results Study Fiqh participant educate. Research implications/limitations: Some of the results of this research still have shortcomings in various aspects. one of them is in selecting the research sample. Originality/value : Although this research still has limitations, the results obtained can be used as a reference for future research with the same study theme.